2000
DOI: 10.1097/00005344-200003000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Fluvastatin and Bezafibrate in Patients with Hyperlipidemia and Persistently High Triglyceride Levels

Abstract: Hyperlipidemia is an important cardiovascular risk factor. Lipid-lowering therapy has been shown to decrease morbidity and mortality in these patients. Combination therapy with a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor and a fibric-acid derivative has been reported to be more efficacious to reduce low-density lipoprotein (LDL) cholesterol and triglycerides but may be associated with an increased risk of myositis. The aim of this study was to investigate the efficacy and tolerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…It is structurally different from the fungal metabolites (lovastatin, pravastatin, and simvastatin) [143,144]. Its effects are similar in most patient groups with 20 to 80 mg daily reducing LDL cholesterol by 22% to 36% and increasing HDL cholesterol by 3.3% to 5.6% [145,146]. In addition to lowering LDL cholesterol levels, 20 to 80 mg dosages of fluvastatin significantly reduced TG levels by 4% to 18%, respectively [145,147].…”
Section: Fluvastatinmentioning
confidence: 99%
“…It is structurally different from the fungal metabolites (lovastatin, pravastatin, and simvastatin) [143,144]. Its effects are similar in most patient groups with 20 to 80 mg daily reducing LDL cholesterol by 22% to 36% and increasing HDL cholesterol by 3.3% to 5.6% [145,146]. In addition to lowering LDL cholesterol levels, 20 to 80 mg dosages of fluvastatin significantly reduced TG levels by 4% to 18%, respectively [145,147].…”
Section: Fluvastatinmentioning
confidence: 99%
“…The most potent triglyceridelowering agents available are fibrates, with the combination of a fibrate and statin providing complementary lipid-lowering effects. In numerous studies, this combination has been shown to control elevations in both LDL cholesterol and triglyceride levels [19][20][21][22][23]. However, concomitant use of a fibrate and a statin has been associated with an increased risk of myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a fibrate is recommended by the ADA for patients with low HDL-C or elevated non-HDL-C who fail to reach their LDL-C target with statin therapy alone [45]. Although several studies have examined the efficacy and tolerability of statin and fibrate combinations in patients with a high risk of CHD [83][84][85][86], there are only limited data available from studies conducted in diabetic subjects. A combination of simvastatin and bezafibrate produced promising results when assessed in a 21-month trial in 148 patients with type 2 diabetes [87].…”
Section: Optimizing the Treatment Of Diabetic Dyslipidemiamentioning
confidence: 99%